Natural Resources and Milling in the middle of the Eighteenth Century: The Tierra de Campos - Ricardo HERNÁNDEZ GARCÍA; José CUBERO GARROTE (Studia Historica: Historia Moderna, 2018)
This paper analyzes the importance of the milling of wheat in the region of the Tierra de Campos in Valladolid in the middle of the 18th century. Despite being an essential operation for the survival of the population, little research has been done on this subject. Thanks to the use of the Respuestas Generales of the Cadastre of Ensenada, it has been possible to locate all the artifacts that grinded the wheat: water mills, windmills and flour mills. The most numerous were the hydraulic mills, which were distributed along the few rivers of the region, leaving many mills that did not have this energy resource without mills. Therefore, its location did not depend on demand, but on the availability of energy. In order to alleviate part of this geographical condition, the use of flour mills powered by mules extended to the lack of water mills.